KUALITAS KOMPOS LIMBAH SOLID SAWIT DENGAN BERBAGAI BIODEKOMPOSER - Najirul Hafizah; Jumar Jumar; Riza Adrianoor Saputra (BPFP Universitas Bengkulu, 2022)
[BIO-COMPOSTING OF SOLID OIL PALM WASTE WITH DIFFERENT DECOMPOSERS AND PHYSICOCHEMICAL CRITERIA FOR COMPOST QUALITY ASSESSMENT] The quantity of produced wastes by oil palm industry is increasing and may lead to significant environmental concerns and the use of these wastes as compost is considered to overcome their negative impacts. However, very few studies have been conducted to develop an effective composting process of the biomass waste using different decomposers. Therefore, the objective of this study was to assess the different physicochemical and biological quality of compost produced by bio-composting of solid oil palm waste with three different commercial decomposers. This study was conducted from September 2021 to November 2021 at the Compost House, Faculty of Agriculture, University of Lambung Mangkurat. A certain period of bio-decomposition process was employed by using commercial bio-decomposers. Physicochemical and biological analyses of the composted solid waste were conducted after decomposer application. The experiment consisted of four treatments (i.e., solid oil palm waste + chicken manure, solid oil palm waste + chicken manure + EM4, solid oil palm waste + chicken manure + M21, and solid oil palm waste + chicken manure + Tangguh) and they were arranged in completely randomized design with three replicates. Results showed that quality of all compost met the SNI 400 standard except for pH, organic-C, and C/N ratio for the treatment without bio-decomposer, pH and C/N ratio for the treatment EM4 bio-decomposer, water content, pH, organic-C, and C/N ratio for M21 bio-decomposer, and pH, organic-C, and C/N ratio for the treatment with Tangguh bio-decomposer, respectively. The maximum germination test obtained was recorded at 70%, 80%, 94%, and 86% in compost media without bio-decomposer, with EM4, 94% with M21, and with Tangguh, respectively. The maximum number of microbes were recorded at 3.2 x 106 µg/g, 2.9 x 105 µg/g, 1.3 x 106 µg/g, and 8.0 x 105 µg/g for compost without bio-decomposer, with EM4, with M21, and with Tangguh bio-decomposer, respectively.